The anti-authoritarian role of dystopias: reflections on Érico Veríssimo’s novel Incident in Antares - Roitberg, Guilherme Prado; Baptista, Fabiana Maria (Universidade Federal de São Carlos, 2019)
The aim of this article is to analyze the relevance of dystopias in the critique to authoritarianism present in the novel Incident in Antares written by Érico Veríssimo. After presenting the main characteristics of utopian thought and dystopia as a literary genre, we investigate how Veríssimo denounced through his dystopian society the deepest contradictions of a country historically plagued by coups d’état and military dictatorships. The article also aims to demonstrate how prevailing Veríssimo’s criticism is, especially regarding to the permanence of authoritarian thought, social inequalities and violations of human rights in Brazil.

O objetivo do presente trabalho consiste em analisar a partir do romance Incidente em Antares de Érico Veríssimo a relevância das distopias na crítica ao autoritarismo. Após apresentarmos as principais características do pensamento utópico e da distopia enquanto gênero literário, investigamos de que maneira Veríssimo denunciou através de sua sociedade distópica as mais profundas contradições de um país historicamente assolado por golpes de Estado e ditaduras militares. O trabalho almeja demonstrar, por fim, a atualidade da crítica de Veríssimo frente à permanência do pensamento autoritário, das desigualdades sociais e das violações aos direitos humanos no Brasil.
O papel antiautoritário das distopias: reflexões sobre o romance Incidente em Antares de Érico Veríssimo
Keywords: Érico Veríssimo; Incidente em Antares; Distopias literárias; Anti-autoritarismo; Literary dystopias; Anti-authoritarianism; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::FILOSOFIA; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA